La inconstitucionalidad de las reformas a la Ley Orgánica de Participación Ciudadana sobre la revocatoria del mandato - Fierro Jarrín, Susana Gabriela (2017)
The purpose of this study is the current regulation of the recall, which is contained by the Organic Law on Citizen Participation and related regulations, and how the reforms carried out pursuant to Judgment No. 01-11-SIO-CC, issued by The Constitutional Court, transforms this mechanism of direct democracy, which constitutes a political right for the citizens to restrict the abuse of power of representatives, into an ineffective institution. Consequently, it is determined that it is necessary to declare the unconstitutionality of said reforms, since they are counterproductive for the attainment of the Constitutional and democratic State that Ecuador declares to be in its Supreme Rule. In order to fulfill the purpose of this essay, the theme is developed in four chapters: the first regarding direct democracy, its concept, characteristics and mechanisms, with special emphasis on the recall; which constitutes the second chapter, that analyzes its particularities and evolution within the Ecuadorian regulatory framework; converging with the third chapter which includes the legal reforms made to this institution; ending with the conclusions, which shows the antinomy of the current regulation in contrast to the constitutional spirit that has this mechanism.